TECHNICAL EFFICIENCY LEVEL OF ISLAMIC BANK IN INDONESIA - Alfu Laila Fiafifah; Darwanto Darwanto (Universitas Negeri Surabaya, 2019)
One of the common measurements used to evaluate a companys performance is the efficiency performance which indicates a companys efficiency score in utilizing inputs to produce outputs. This study aims to evaluate the performance of state-owned Indonesian Islamic banks by measuring their technical efficiency along with the determinant factors of their efficiency over the period 2014-2017. In this study, DEA, a non-parametric technique method, is employed to measure the efficiency of four state-owned Indonesia Islamic banks. Another method, Tobit-regression, is used to identify the determinant factors of their efficiency. Four state-owned Indonesian Islamic banks are chosen as the object of this study, namely Bank Syariah Mandiri, BNI Syariah , Bank Rakyat Indonesia Syariah, and BTN Syariah. The results of calculation using DEA methos show that the average efficiency level of all state-owned Indonesian Islamic banks over four consecutive yerars is 100%. It means that all the state-owned Indonesian Islamic banks operating in Indonesia have been able to optimize all their resources and are considered efficient over the period 2014-2017. Tobit-regression model results show that bank size, capitalization, and profitability significantly affect all state-owned Islamic banks efficiency, while bank expenses do not have a significant effect on their efficiency.